2014
DOI: 10.1007/s10562-014-1399-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalysis I: Synthesis of Metal and Bimetallic Nanoparticles and Porous Oxides and Their Catalytic Reaction Studies

Abstract: In recent heterogeneous catalysis, much effort has been made in understanding how the size, shape, and composition of nanoparticles and oxide-metal interfaces affect catalytic performance at the molecular level. Recent advances in colloidal synthetic techniques enable preparing diverse metallic or bimetallic nanoparticles with welldefined size, shape, and composition and porous oxides as a high surface support. As nanoparticles become smaller, new chemical, physical, and catalytic properties emerge. Geometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 76 publications
1
65
0
Order By: Relevance
“…The functional properties can be tuned by modifying the size, shape and composition of the synthon along by studying state of art of the synthetic method with pH control which helps to design a device for their technological applications with synergic effects to control the nucleation and its growth. Understanding the nucleation and growth process by self-assembling helps to integrate functional structures via optimizing hydrolysis and kinetic process based on electro-negativity of metal ion (Klein 1988;Brinker and Scherer 1990;Sakka 2004;Szafert et al 2008;Grado-Caffaro 2008;Bilecka and Niederberger 2010;Bang and Suslick 2010;Liu et al 2011;Hassan et al 2012;Precht and Campbel 2013;An and Soorrjai 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional properties can be tuned by modifying the size, shape and composition of the synthon along by studying state of art of the synthetic method with pH control which helps to design a device for their technological applications with synergic effects to control the nucleation and its growth. Understanding the nucleation and growth process by self-assembling helps to integrate functional structures via optimizing hydrolysis and kinetic process based on electro-negativity of metal ion (Klein 1988;Brinker and Scherer 1990;Sakka 2004;Szafert et al 2008;Grado-Caffaro 2008;Bilecka and Niederberger 2010;Bang and Suslick 2010;Liu et al 2011;Hassan et al 2012;Precht and Campbel 2013;An and Soorrjai 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Bimetallic oxide exhibits novel physico-chemical properties that can be tailored with composition, size and atomic ordering. Metal ion plays a crucial role in balancing the thermodynamic-kinetic parameters to control functional behavior due to its coordination with metal ions and also tuning of surface morphology leads to the formation of nanostructure material with high performance (Klein 1988;Brinker and Scherer 1990;Kessler 2003;Sakka 2004;Szafert et al 2008;Bilecka and Niederberger 2010;Hassan et al 2012;Precht and Campbel 2013;An and Soorrjai 2015). During synthesis, we focused the phase separation with non-aggregated particles by retaining stoichiometric ratio under control.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Specific examples include the systems of Fe-Ru for efficient Fischer-Tropsch synthesis, [2] Al-Fe as aP d-free hydrogenation catalyst, [3] Rh-Pd for selectiveC Oo xidation, [4] and Pt-Co for renewable fuel generation [5] or the activation of Au in bimetallic systems. [6] Several studies have also demonstrated that bimetallic nanoparticles can outperform their monometallic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Therefore, the alloyingo fp recious metals with an abundant, less-precious metal is of particular interestn ot only to improvet he catalytic properties but also for effective cost reduction. [8] In contrastt ob imetallic M-Pd or M-Pt systems (M:m etal), bimetallic systems of Ir and Os have been barely addressed, in general.…”
Section: Introductionmentioning
confidence: 99%
“…Metal NPs have emerged as a new class of catalysts with physical and chemical properties distinct from individual mononuclear metals and bulk surfaces [5]. In this context, NPs are attractive catalyst candidates since they combine high activity and selectivity with improved recyclability possibilities.…”
Section: Introductionmentioning
confidence: 99%